Destiny profile of a 413.5 m deep fresh core recovered at Mizuho Station, East Antarctica - Nakawo,Masayoshi; Narita,Hideki (1985)
P(論文) Within a month after the core recovery, the density data were obtained from the dimensions and the weights of the core samples and by the hydrostatic method. The density data were corrected for the surface effect with considerations of the bubble concentration and the average bubble size. A method has been presented to estimate the in situ density value (without cracks) from the nominal density data with cracked samples based upon the data on total gas content. This method has been applied to the data of deep portion (below 135m depth), where the core was cracked considerably. A reasonable depth profile of in situ density was thus estimated, which indicated that the shrinkage of trapped air bubbles was the main densification process of ice after the bubble close-off. departmental bulletin paper